Нові наукові і прикладні результати досліджень ефективності використання пиловугільного палива при виробництві чавуну і випалі вапняку - Семенов, Ю. С.; Подкоритов, О. Л.; Горупаха, В. В.; Семіон, І. Ю.; Оробцев, А. Ю.; Нестеров, О. С.; Шумельчик, Є. І.; Пустовой, С. М.; Гапоненко, О. А.; Соловйов, В. В. (Physico-technological Institute of Metals and Alloys, 2023)
The article presents the main results of cooperation of the Z.I. Nekrasov Iron & Steel Institute of the NAS of Ukraine and PJSC “Dneprovsky Iron & Steel Integrated Works” in 2017–2019 on the subject of blast furnace production and development of technology of injection of pulverized coal in rotary kilns of lime burning. There have been highlighted the results of a set of measures to ensure the rational distribution of coal dust in the blast furnace tuyeres to align the thermal state of the tuyere zone along the circumference of blast furnaces; the results of the use of the technology of sharing pulverized coal and natural gas; recommendations for blowing of blast furnaces after stopping for a period exceeding the allowable one, without prior release of freezing iron, due to which blast furnaces were accidentally put into operation with the achievement of the planned targets; the results of the use of information from probes that measure the gas flow temperature above the surface of the charge to further substantially adjust the furnace charging modes by means of a developed expert module that generates the charging mode corrective actions to support the decision-making of technological personnel; the results of applying a set of measures to prevent blast furnace malfunction when using pulverized coal in the amount of more than 140 kg/t of cast iron without the use of special flushing materials; results of efficiency of the spent technology of use in the composition of blast furnace charge of manganese-containing materials on a constant basis and results of implementation of the method of diagnostics of the efficiency of the mechanisms of installation of pulverized coal in a rotary kiln of lime with the further development of recommendations for adjusting the parameters of the operation of the setting mechanisms.